Bagaimana pengaruh tutup, bentuk dan ukuran kemasan terhadap pembelian produk air mineral Aqua dalam kemasan click and go? - Benyamin Regi; Muhammad Arfa (Universitas Bumigora, 2022)
Animation media has a very important role in improving the initial reading ability of the first graders of SDI Wolomarang. This study aims to determine the extent to which an animation media can be used and measure the development of reading skills in elementary grade students. At an early age, students are more familiar with visually appealing and easy-to-remember media than boring verbal presentations. This study uses quantitative research methods with data collection techniques including tests and observations, analyzed using the T-test. From the results of the T-test calculation, there is a t-count of 2.410 and a t-table with dk = 15 and a significant level = 0.05 is 1.753. It can be concluded that t-count > ttable (2.410>1.753) so that Ho is rejected and Ha is accepted. From these results, it can be seen that there is an effect of using animation media on the initial reading ability of the first graders of SD InpresWolomarang. Thus, it can be concluded that the students' initial reading ability and class 1 students' learning outcomes have changed for the better after using animation media in the experimental class.